Exploiting the Impact of Sociodemographics in the Diagnosis of Central Nervous System Tumors in Childhood - Marcela Yasmin Leroy; Luiz Fernando Lopes; Raniela Ferreira Faria; Thaissa Maria Veiga Faria; Denise Leonardi Queiroz Prado; Welinton Yoshio Hirai; Bruna Minniti Mançano (Brazilian Journal of Oncology)
Introduction Central nervous system (CNS) tumors are the most common solid tumors in childhood, comprising 20% of all neoplasms in that age. Besides, they constitute the biggest cause of morbidity and mortality among childhood tumors, and about two thirds of the surviving patients have sequelae. The build-up of sequelae due to neoplastic growth is directly related with the time until diagnosis. Therefore, late diagnosis has a negative influence on the prognosis.